1992
DOI: 10.1093/oxfordjournals.humrep.a137538
|View full text |Cite
|
Sign up to set email alerts
|

How well does ultrasonographic measurement of endometrial thickness predict the results of histological dating?

Abstract: In this study, transabdominal ultrasonographic measurement of endometrial thickness was performed prior to sampling of the endometrium for histological examination in regularly cycling women. In the natural cycles, the results of ultrasonography and histological dating were significantly correlated (r = 0.76, P less than 0.0001, n = 63). Endometrial histology was likely to be proliferative if the thickness was less than 8 mm, and likely to be secretory if the thickness was greater than 9 mm. However, for a giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…In three cases follicular rupture was observed on the same day as the LH peak, which is earlier than normal (Ritchie, 1985), and might have been caused by the pressure of the vaginal probe during the investigation. Previous ultrasonographic studies of normal endometrial development have mostly been performed on women in stressful situations such as during investigation and treatment of infertility (Randal etal., 1989;Yoshimitsu et al, 1989;Lenz and Lindenberg, 1990;Grunfeld et al, 1991;Li et al, 1992), while the present study investigated healthy volunteers. Women in a stressful situation, such as infertility, are probably not an optimal group for studying the normal events of the menstrual cycle (Andrews et al, 1992).…”
Section: Discussionmentioning
confidence: 73%
“…In three cases follicular rupture was observed on the same day as the LH peak, which is earlier than normal (Ritchie, 1985), and might have been caused by the pressure of the vaginal probe during the investigation. Previous ultrasonographic studies of normal endometrial development have mostly been performed on women in stressful situations such as during investigation and treatment of infertility (Randal etal., 1989;Yoshimitsu et al, 1989;Lenz and Lindenberg, 1990;Grunfeld et al, 1991;Li et al, 1992), while the present study investigated healthy volunteers. Women in a stressful situation, such as infertility, are probably not an optimal group for studying the normal events of the menstrual cycle (Andrews et al, 1992).…”
Section: Discussionmentioning
confidence: 73%
“…Recently, there have been attempts to improve endometria] dating by more modern approaches (Li et al, 1988(Li et al, , 1992Li and Cooke, 1991). In summary, these studies suggest that it is unlikely that ultrasonographic measurement of endometrial thickness can replace histological examination of the endometrium in the evaluation of the luteal phase (Li et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, these studies suggest that it is unlikely that ultrasonographic measurement of endometrial thickness can replace histological examination of the endometrium in the evaluation of the luteal phase (Li et al, 1992). However, the precision of endometria] dating may be improved if chronological dating is based on the luteinizing hormone surge or the time of follicle rupture (determined by serial ultrasonography), and if histological dating is based on morphometry, a quantitative and objective histological technique (Li et al, 1988;Li and Cooke, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between increased endometrial thickness and pregnancy rates and further explained that this effect is dependent on the age of the patient, duration of stimulation, and embryo quality (Rabinowitz et al, 1986;Zhang et al, 2005). Contrary to these data, other studies show that measurement of endometrial thickness had no predictive value for pregnancy in ART Glissant et al, 1985;Ivanovski et al, 2007a;Li et al, 1992;Welker et al, 1989). Amir et al (2007) reported that the possibility of a thick endometrium in IVF administered women over the age of 40 is less than that of the younger patient group; however, he also reported that pregnancy rate increases in the presence of thick endometrium.…”
Section: Endometrial Thicknessmentioning
confidence: 99%